Other Others : The Political after the Talmud - Dolgopolʹskiĭ, S. B. (Sergeĭ Borisovich) (Book collections on Project MUSE., 2018)
"Dolgopolski introduces to political theory the concept of "other others," those earthly extraterrestrials who are not and cannot be marked as bearing any "original" belonging to a recognized land. Moving between the modern political figure of "Jew" and the late ancient texts of the Talmud, the book ultimately arrives at a demand to think earth anew, beyond notions of territory, land, nationalism or internationalism, or even universe that have hitherto defined it. At the junction of classical rabbinic thought and contemporary political theory, Dolgopolski seeks to expand the horizon for thinking earth in the face of each new challenge and each new responsibility that greets us"--